Elderly care in Islamic legislation (Journal of the College of Basic Education, 2023)
Praise be to God, Lord of the worlds, and prayers and peace be upon the master of the prophets and messengers, our beloved Muhammad, and upon his pure God and his chosen companions.But after:Voices and calls calling for caring for the elderly and adopting their rights have been heard since the second half of the last century in the face of the bitter impact of them, and the tragic incidents that are repeated for them and which are mentioned in the daily newspapers. and other political.And if this concern did not emerge except in the past years, Islam organized this concern in its finest details and emphasized it fourteen centuries ago, and this was reflected in the behavior and practices of the members of the Muslim community at that time in their dealings with the elderly, and it did not only regulate rights, but also called for their protection and demanded that everyone take care of them between For the elderly, meals and provisions that are appropriate to their age and energy are legislated for them. And you will really see that when you read this research that is in your hands.The secret of this is that the Islamic Sharia includes bringing interests in all their subtlety and majesty, and averting corruption in its entirety, subtlety and majesty. And Imam al-Juwayni was right when he said: ((He who does not underestimate the virtues of the Shari`ah and does not know its secrets and hidden secrets will escape from the control of the Shari`a, so he will not be preceded by a previous honor, unless he researches the Shari`ah to familiarize it with it or informs from it about the status of the Shari`a))(*) because the house of this Shari`ah He is the Creator, the All-Knowing of the conditions of His servants, the Wise of His actions, the Merciful of the souls of His creation, for He is the Mighty, the Wise